Iodine-Catalyzed [3+2]-Cyclization of Substituted Benzylidenemalononitriles and Ethyl Glycinate Hydrochloride: Direct Access to 5-Amino-1H-pyrrole-2-carboxylates - Su, Zhenjie; Wang, Shan; Luo, Naili; Wang, Cunde (Synlett, 2020)
An iodine-catalyzed [3+2]-cycloaddition reaction of substituted benzylidenemalononitriles and ethyl glycinate hydrochloride in DMF has been developed for the synthesis of 5-amino-1H-pyrrole-2-carboxylates. This efficient method provides access to a variety of structurally diverse pyrrole-2-carboxylate derivatives. The structure of a typical product was confirmed by X-ray crystallography.
Keywords: [3+2]-cycloaddition; ethyl glycinate hydrochloride; benzylidenemalononitrile; aminopyrrolecarboxylates; aromatization